Challenges of Open Distance Learning (ODL) among ENT530 students / Zainuddin Mohd Piah ... [et al.] - Mohd Piah, Zainuddin; Mustapa, Siti Noor Syalwani; Anuar, Azyyati (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
The global crisis due to the outbreak of the COVID-19 has delayed conventional teaching and learning. Still, it has made the lecturer's task more challenging as they have to adapt new norms that require the teaching and learning process by implementing Open and Distance Learning or so-called ODL. ODL is any learning activity within formal, informal, and non-formal learning activities facilitated by information and communication technologies to lessen distance, both physically and psychologically, and increase interactivity and communication among learners, lecturers, and learning sources (IGI Global, 2020). Similarly, as defined by Kaplan and Haenlein (2016), distance education offers participation in open access through the internet and other networks, and it is also known as Massive Open Online Courses (MOOCs). In other terms, it could be a virtual classroom, online learning, e-learning, etc. According to Kim and Bonk (2006), technology has played and continues to play an essential role in the development of online education. The way technology is being used for teaching and learning has enhanced people's knowledge and also proved to have a positive impact on the education process.